Hybrid opto-chemical doping in Ag nanoparticle-decorated monolayer graphene grown by chemical vapor deposition probed by Raman spectroscopy. (16th January 2017) - Maiti, R; Haldar, S; Majumdar, D; Singha, A; Ray, S K
Abstract: The novel opto-chemical doping effect in Ag nanoparticle-decorated monolayer graphene grown by chemical vapor deposition has been investigated using Raman spectroscopy for the first time. We used both noble metal nanoparticles and optical excitation, in a hybrid opto-chemical route, to tune the doping level in graphene. Metal nanoparticle-induced chemical effects and laser power-induced substrate effects alter the doping nature of graphene from p- to n-type. Compared with earlier studies, the proposed method significantly lowers the laser intensity required for optical power-dependent doping, resulting in prevention of damage to the sample due to local heating. Some other interesting observations are the enhanced peak intensity in the Raman spectrum of graphene, enhancement of the D-band intensity and the introduction of G-band splitting. This novel, cheap and easily implemented hybrid optical–chemical doping strategy could be very useful for tuning graphene plasmons on the widely used Si/SiO2 substrates for various photonic device applications.